2018
DOI: 10.3390/s18010278
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive Strain Sensor Based on a Novel Mach-Zehnder Interferometer with TCF-PCF Structure

Abstract: A highly sensitive strain sensor based on a novel fiber in line Mach-Zehnder interferometer (MZI) was demonstrated experimentally. The MZI was realized by splicing a section of photonic crystal fiber (PCF) with the same length of thin core fiber (TCF) between two single mode fibers (SMFs). The fringe visibility of MZI can reach as high as 20 dB in air. In particular, the strain sensitivity of −1.95 pm/με was achieved within a range from 0 to 4000 με. Furthermore, the strain properties of different length of MZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Meanwhile, the MZI with different length of PCF also shown high fringe visibility, the max attenuation depth of which were about 17.2 dB, 20.3 dB, 19.9 dB and 24.1 dB, respectively, as illustrated in Figure 3 . The max fringe visibility of our proposed MZI with SMPS fiber structure was higher than those of MZI with TCF-MMF-TCF structure (21 dB) [ 34 ] or MMF-TCSMF-MMF structure (14 dB) [ 35 ], MZI based on asymmetrical twin core fiber and multimode fiber (15 dB) [ 36 ] and some PCF interferometer structures, such as PCF-MZI with two waist-broadened tapers (11 dB) [ 37 ] or with up-tapered joints (11.5 dB) [ 38 ], normal PCF-MZI (21 dB) [ 28 ], TC-PCF MZI (10 dB) [ 16 ], TCF-PCF structure MZI (20 dB) [ 39 ] and S-tapered PCF (12 dB) [ 40 ]. In addition, it can be observed that the insertion loss of the proposed MZI is larger than that of MZI with SMF-PCF-SMF structure [ 8 ], which is due to the increase in the number of fusion.…”
Section: Experiments Results and Discussionmentioning
confidence: 99%
“…Meanwhile, the MZI with different length of PCF also shown high fringe visibility, the max attenuation depth of which were about 17.2 dB, 20.3 dB, 19.9 dB and 24.1 dB, respectively, as illustrated in Figure 3 . The max fringe visibility of our proposed MZI with SMPS fiber structure was higher than those of MZI with TCF-MMF-TCF structure (21 dB) [ 34 ] or MMF-TCSMF-MMF structure (14 dB) [ 35 ], MZI based on asymmetrical twin core fiber and multimode fiber (15 dB) [ 36 ] and some PCF interferometer structures, such as PCF-MZI with two waist-broadened tapers (11 dB) [ 37 ] or with up-tapered joints (11.5 dB) [ 38 ], normal PCF-MZI (21 dB) [ 28 ], TC-PCF MZI (10 dB) [ 16 ], TCF-PCF structure MZI (20 dB) [ 39 ] and S-tapered PCF (12 dB) [ 40 ]. In addition, it can be observed that the insertion loss of the proposed MZI is larger than that of MZI with SMF-PCF-SMF structure [ 8 ], which is due to the increase in the number of fusion.…”
Section: Experiments Results and Discussionmentioning
confidence: 99%
“…The experimental setup for strain testing is illustrated in Reference [24]. The proposed sensor was mounted on two translation stages.…”
Section: Resultsmentioning
confidence: 99%
“…Previous papers have increased the sensitivity of FBG Bragg gratings using microstructures through tapering technology [58], and Bragg gratings based on grating configurations [59] have been introduced by previous studies. In addition, various previous studies have improved the maximal function of the Bragg grating sensor and investigated the sensing of various characterizations of the measurement range [60][61][62][63].…”
Section: Fiber Bragg Grating Waveguide Devicesmentioning
confidence: 99%